PENGARUH FoMO, KESENANGAN BERBELANJA DAN MOTIVASI BELANJA HEDONIS TERHADAP KEPUTUSAN PEMBELIAN TIDAK TERENCANA DI E-COMMERCE SHOPEE PADA WAKTU HARBOLNAS - Yunita Ramadhani Ratnaningsih DS; Anissa El Halidy (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Unplanned purchase decisions not only occur in offline stores but also in e-commerce. This study aims to determine the effect of FoMO, Shopping Pleasure, and Hedonic Shopping Motivation on unplanned purchase decisions on e-commerce Shopee during Harbolnas. The research method used is quantitative by distributing questionnaires to 100 respondents. The sampling method used non-probability sampling with purposive sampling technique. The data analysis used is validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis testing with the help of SPSS 23 as a test tool. The results showed that the variables FoMO, Shopping Pleasure, and Hedonic Shopping Motivation had an effect on unplanned purchasing decisions on Shopee e-commerce during Harbolnas.